The Jury Speaks: Jury Riders in the Nineteenth and Twentieth Centuries. Issue 4 (6th November 2018) - Coen, Mark; Howlin, Niamh
ABSTRACT: Jury riders are statements that accompany verdicts. This article examines the use and contents of jury riders in Ireland and England in the nineteenth and twentieth centuries. It reveals the wide variety of contexts in which jurors appended statements to their verdicts and suggests a typology of jury riders in order to better understand the motivations behind such statements. It asks why jury riders survived into the twentieth century and considers the factors that led to riders' ultimate decline.